Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1073/pnas.1916987117
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into the interactions of dynein regulator Ndel1 with neuronal ankyrins and implications in polarity maintenance

Abstract: Ankyrin-G (AnkG), a highly enriched scaffold protein in the axon initial segment (AIS) of neurons, functions to maintain axonal polarity and the integrity of the AIS. At the AIS, AnkG regulates selective intracellular cargo trafficking between soma and axons via interaction with the dynein regulator protein Ndel1, but the molecular mechanism underlying this binding remains elusive. Here we report that Ndel1’s C-terminal coiled-coil region (CT-CC) binds to giant neuron-specific insertion regions present in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 54 publications
3
17
0
Order By: Relevance
“…Furthermore, the dynein regulator Ndel1 binds to the AnkG tail (asterisks in Fig. 3 B), and this interaction is essential for AIS filter functions (Ye et al, 2020). In agreement with these functional studies, EM analyses suggest that a fraction of MTs are in contact with the undercoat ( Fig.…”
Section: Introductionsupporting
confidence: 63%
“…Furthermore, the dynein regulator Ndel1 binds to the AnkG tail (asterisks in Fig. 3 B), and this interaction is essential for AIS filter functions (Ye et al, 2020). In agreement with these functional studies, EM analyses suggest that a fraction of MTs are in contact with the undercoat ( Fig.…”
Section: Introductionsupporting
confidence: 63%
“…and ankyrin-G with 2:1 stoichiometry (Ye et al, 2020). The crystal structure of the ankyrin-B-NDEL1's CT-CC complex revealed a stable 5-helix bundle dominated by hydrophobic interactions spread across six distinct interaction layers (Ye et al, 2020).…”
Section: Microtubules and Microtubule-associated Proteinsmentioning
confidence: 99%
“…Ankyrin‐G is necessary for NDEL1 localization to the AIS, where it promotes the polarized distribution of dendritic cargo by reversing the direction of transport of somatodendritic vesicles at the AIS (discussed below; Kuijpers et al, ). A recent report showed that NDEL1's C‐terminal coiled‐coil region (CT‐CC) binds a similar ~70‐amino acids stretch within the inserted region of both ankyrin‐B and ankyrin‐G with 2:1 stoichiometry (Ye et al, ). The crystal structure of the ankyrin‐B‐NDEL1's CT‐CC complex revealed a stable 5‐helix bundle dominated by hydrophobic interactions spread across six distinct interaction layers (Ye et al, ).…”
Section: Functional Roles Of the Spectrin And Ankyrin Assemblies In Nmentioning
confidence: 99%
See 2 more Smart Citations